Strategi Pengembangan Pariwisata Pantai di Kota Ternate, Provinsi Maluku Utara - Latif, Julifa M; Rustiadi, Ernan; Hidayat, Janthy T (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2023)
The city of Ternate has great potential in the field of tourism, with a strategic geographicallocation has a high level of tourist visits both local and foreign tourists, has a variety of touristobjects and attractions and has the characteristics of the city as a coastal city (waterfront city).However, currently the tourism potential along the coast of Ternate City has not been maximallyexplored. This study aims to 1) analyze beach tourism objects that have developed, those that havethe potential to be developed and those that have less potential to be developed; 2) analyze thefactors that attract tourists; 3) analyze the strategy of developing tourism objects. several methodsused include Multi-Criteria Evaluation (MCE), binary logistic regression, and AWOT combinedAnalytic Hierarchy Process (AHP) and Strenghts, Weakness, Opportunities, and Threats (SWOT).Based on the results of the assessment of physical parameters and institutional, socio-cultural andeconomic parameters, Of the nine identified beach tourism objects, five of them have beendeveloped, two tourism objects are included in the category of tourism objects that have thepotential to be developed and the other two have less potential to be developed. Factors drivingand attracting tourist interest in beach tourism objects in Ternate City consist of, Age; Visitfrequency; one-time visit fee and facilities. The priority strategy for developing beach tourismobjects in Ternate City consists of: developing tourism objects by taking advantage of theiruniqueness and increasing promotion; program upgrade community based tourism, improvemaintenance event-event related to tourism, improvement of accommodation facilities;development of the tourism sector as a leading sector, reinforces existing regulations in terms oflicensing of C minerals in tourist areas.